Mechanical Ventilation embedded in Neonatal Incubator - Mugruza-Vassallo, C. A.; Castillón-Lévano, C. B.; Román-Linares, H. (Revista Mexicana de Ingenieria Biomedica, 2018)
A neonatal life support equipment (ESVIN) employing simultaneously thermal therapy and ventilatory (pneumatic) therapy is presented in a single kit to provide pulmonary ventilation with warm, moistened and oxygen enriched air in a warm, humidified and sterile environment. The invention behind ESVIN provided simultaneously pulmonary ventilation and incubation having optimized the minimization of water condensation in the corrugated pipe and offered the additional feature of avoiding the mobilization and / or disconnection of the neonate to perform certain procedures such as: surgeries and intubations, among others. ESVIN has an access to newborns of less than 2 s and non-visible water condensation. The main results in thermal control were a stabilization time in the newborn compartment of 75 minutes for the temperature of 36 °C and a stabilization of the temperature of the skin of the neonate of 58 minutes.